PENGARUH PEMANFAATAN APLIKASI DIGITAL TERHADAP PEMBERDAYAAN UMKM DI KABUPATEN KUTAI TIMUR - Muhamad Yazid Bustomi; Nani Rohaeni; Dhani Aryanto; Faizal Faizal (Universitas Bina Sarana Informatika, 2021)
The objectives of this study were (1) to determine the social, economic, and environmental impacts of MSMEs Partners after using digital applications (2) to identify the effects of the utilization digital applications on the empowerment of MSMEs Partners. The sampling technique used saturated sampling, where all members of the MSMEs partners who had used digital applications in their business were used as samples in this research. The data analysis method was descriptive statistics with SPSS program, and SEM-PLS with the SmartPLS version 3.0 software. The results showed that the highest mean value of descriptive statistics was the economic impact with a value of 3.94 and a standard deviation of 0.70. It stated the utilization of digital applications has an economic impact on MSMEs Partners Community Development Officier PT. KPC. The variables (impact) of the utilization digital applications that have a significant effects on the empowerment of MSMEs Partners are economic impacts and social impacts, while environmental impacts do not have a significant effect on the empowerment of MSMEs Partners. Keywords: Digital Applications, Empowerment MSMEs, Partial Least Square.